Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Pos Indonesia Tangerang Selatan - Nur Afifah Amir; Muhamad Guruh (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of this study was to determine the effect of leadership style and work discipline on employee performance at PT Pos Indonesia South Tangerang. The method used is quantitative. The sampling technique used saturated sampling, namely 60 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study are Motivation has a significant effect on employee performance with a coefficient of determination of 79.2% and hypothesis testing obtained t count> t table or (10.853> 2.001). Work discipline has a significant effect on employee performance with a coefficient of determination of 73.9% and hypothesis testing obtained t count> t table or (4,032> 2,001). Motivation and work discipline have a positive and significant effect on employee performance with the regression equation Y = 5.318 + 3.45X1 + 0.678X2. The coefficient of determination is 79.2% while the remaining 20.8% is influenced by other factors. Hypothesis testing obtained the value of F count> F table or (108.695> 2.001). And the significant value of the results of X1 and X2 on Y (0.001 <0.05) then H0 is rejected and H3 is accepted, meaning that it can be concluded that there is a positive and significant influence between motivation and work discipline on employee performance at PT Pos Indonesia South Tangerang.